Benefit Planning Management for ITSM: Evaluating Benefit Realization Frameworks - Mcloughlin, Stuart; Scheepers, Helana; Wijesinghe, Ravinda (ACIS, 2014)
The popularity of ITSM frameworks such as ITIL is indicative of the perception amongst practitioners that there are key benefits to be derived, at both the organizational level and the functional level. Various studies indicate that a comprehensive benefits realization model is required to ensure that organizations maximize benefits of ITSM projects. Although there is a call for more research in this area, very few ITSM related studies explore such benefits realization models with any level of detail. This paper is a conceptual study that reviews the literature on benefits realization models and applies and adapts prior learning from the Enterprise System, Enterprise Resource Planning literature and the general Information Systems literature on Benefit Realization Management to inform the research and practice in the ITSM field. We posit that, based on the unique characteristics of ITSM that the most likely benefits realization model that should be explored in an ITSM context is the Cranfield Process Model of Benefits Management.